Etika Bisnis Pengusaha Muslim Terhadap Pelayanan Konsumen Dalam Meningkatkan Daya Beli Masyarakat (Studi Kasus Pedagang Pusat Pasar Kota Padangsidimpuan) - Siregar, Rosnani (Institut Agama Islam Negeri Padangsidimpuan, 2015)
Urgency business can not be underestimated. Businesses play a vital role (important) in the social life of all time. Where economic power has the same meaning with political forces, so the urgency of the business can affect all levels of individual, social, regional, national and international. Thus any economic system as long as it guarantees necessary to uphold justice must be human. The involvement of Muslims in the trade is strongly associated with their religious understanding of the principles of life that always put the stocking of mercy for all the worlds. In this context Muslim traders consider trading business in a noble work and the legitimacy of the prophet of Allah. Traders may do with the accounts payable system to market consumer goods. Accounts payable that do not contain elements of usury. Consumers should not neglect the payment of debts to merchants, so that no dispute. In determining the price of the merchandise, the merchant must provide the appropriate price to the market price of each consumer. Merchants must provide khiyar rights for consumers, according to the rules khiyar in Islamic law. If it has been so ethical entrepreneurs in serving customers, then customers will shop and increase purchasing power in Muslim merchant stores